Body image change in obese and overweight persons enrolled in weight loss intervention programs: a systematic review and meta-analysis. - Hai-Lun Chao (PLoS ONE)
To report the results of a systematic review and meta-analysis examining whether weight loss interventions improve body image in obese/overweight individuals. Medline, Current Contents, and the Cochrane database were searched to identify studies involving obese/overweight adults who were enrolled in weight loss interventions in which body image was quantitatively assessed. Outcomes assessed were changes in body shape concern, body size dissatisfaction, and body satisfaction (intervention vs comparator/control group). Seven studies were included in the systematic review (4 in the meta-analysis). All but 1 study involved female participants only. The type of weight loss intervention varied between studies as did the type of control/comparator group. In 3 studies, there was no significant difference in body image outcomes, whereas in 4 studies, improvement in body image was significantly more pronounced in the intervention vs the control/comparator group. Meta-analysis revealed that improvements in body shape concern (standardized difference: -0.52; 95% confidence interval [CI]: -1.04 to 0.00), body size dissatisfaction (standardized difference: -0.66; 95% CI: -0.88 to -0.45), and body satisfaction (standardized difference: 0.74; 95% CI: 0.09 to 1.38) significantly favored the intervention over the comparator/control group (P<0.05). The results of this systematic review/meta-analysis lend support to the notion that weight loss interventions may improve body image. This is a noteworthy finding that has clear clinical applicability because body image affects psychological well-being and the ability of an individual to maintain weight loss. Future research should determine which weigh loss interventions are associated with optimal improvements in body image and maintenance of weight loss.